ANALISIS STRUKTUR, JENIS, DAN FUNGSI KALIMAT DALAM KONTEN AKUN INSTAGRAM @kata.cerdas (KAJIAN SINTAKSIS BAHAS INDONESIA) - Wildan, Wildan Aldiansyah (Jurnal PENEROKA, 2025)
@kata.cerdas account using a descriptive qualitative approach. The main focus is identifying sentence types simple, compound, and complex as well as syntactic elements such as subject, predicate, object, complement, and adverbial, which are used to convey motivational messages effectively. Data were purposively collected from captions posted between 2023 and 2024, covering various themes such as life reflection, motivation, and inspirational quotes. The findings reveal that the sentence structures used exhibit unique characteristics that highlight clarity, emotional closeness, and high communicative effectiveness. Complex sentences are predominantly used to deliver reflective messages, while simple sentences are preferred for short affirmations. This study contributes to digital linguistic studies and offers an effective communication model that can be adopted by motivational content creators. Social media is positioned not merely as a visual platform but as a strategic space for building personal interaction through appropriate language choices. Therefore, selecting the right sentence structure plays a crucial role in enhancing message appeal and increasing audience engagement in dynamic and interactive digital communication.